A Research for the Determination of the Relationship between Organizational Conflict Management and Organizational Alienation - Oya Korkmaz; Sibel Aydemir (International Review of Management and Marketing, 2015)
Our study researched at which level organizational conflict affected organizational alienation and what kind of a relationship there is between organizational conflict dimensions and organizational alienation in the institutions reviewed by us. Our study also examined how organizational conflict and organizational alienation are influenced by the demographical variables including sex, marital status, income status, education and job experience. Necessary data was collected by survey method in our study. The surveys were made to white collar employees who are working for the leading logistics companies of the industry operating in Mersin and Zonguldak provinces of Turkey. The data which was obtained from the surveys was interpreted after being analyzed in SPSS statistic package program and it was aimed to make it guiding for the decision makers while creating new human resource policies in their institutions.